2020
DOI: 10.1155/2020/7615848
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Alkali‐Activated Copper‐Nickel Slag Material

Abstract: A copper-nickel slag-based alkali-activated cementing material (CNSCM) for backfilling was prepared using copper-nickel slag as a raw material and sodium silicate (SS) as an activating agent. The effects of SS content (6%, 8%, and 10%) and curing humidity on the compressive strength of CNSCM were investigated using an electronic universal testing machine. Types of hydration products and microstructures were analyzed by X-ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…NaOH activators resulted in the fastest product structural build-up. [15] investigated the influence of parameters such as activator dosage, curing condition, and curing age on microstructural as well as strength development of alkali-activated copper-nickel slag. Optimum Na 2 SiO 3 dosage was 8% for compressive strength of 17 MPa at 28 days.…”
Section: -2mentioning
confidence: 99%
“…NaOH activators resulted in the fastest product structural build-up. [15] investigated the influence of parameters such as activator dosage, curing condition, and curing age on microstructural as well as strength development of alkali-activated copper-nickel slag. Optimum Na 2 SiO 3 dosage was 8% for compressive strength of 17 MPa at 28 days.…”
Section: -2mentioning
confidence: 99%
“…is indicated that more CH is detected in CP sample, which means the CH in CP-10, CP-30, and CP-50 samples was consumed by the pozzolanic reaction of the Cu-Ni slag. e reaction of pozzolanic materials is generally that the active parts SiO 2 , Al 2 O 3 , and Ca(OH) 2 react with pozzolanic materials in the following form [10]:…”
Section: E Pozzolanic Reaction Of Cu-ni Slag Was Activated Bymentioning
confidence: 99%
“…e existing research [4][5][6] shows that the nonferrous smelting slag has certain pozzolanic activity or potential hydraulic property. Compared with the water-quenched blast furnace slag [7][8][9][10][11][12], the nonferrous smelting slag has the problem of the relatively low pozzolanic activity or potential hydraulic property, and the comprehensive utilization added value is low. erefore, the relevant research and application are relatively few, and the overall utilization rate is not high.…”
Section: Introductionmentioning
confidence: 99%
“…AAS had the characteristics of low-carbon dioxide emissions and recycling of industrial solid waste, and the advantages of its good early-phase mechanical properties, high-temperature resistance, and strong corrosion resistance had been proved by many studies [5]. However, the disadvantages of AAS were the too fast setting time, cumbersome preparation process, and alkali corrosive damage; these points restricted the AAS application and promotion.…”
Section: Introductionmentioning
confidence: 99%